2021
DOI: 10.3177/jnsv.67.417
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Homocysteine with B Vitamins and Zinc in Serum Levels of Patients with Type 2 Diabetes Mellitus: A Cross-Sectional Study

Abstract: The association of homocysteine metabolism-related nutrients along with renal function to homocysteine levels is not well known in patients with type 2 diabetes mellitus (T2DM). We investigated the relevance of kidney function, albuminuria, and nutritional factors to serum homocysteine in T2DM patients. This cross-sectional study enrolled 149 T2DM patients (96 men and 53 postmenopausal women), and patient characteristics and laboratory data including kidney-related data [glomerular filtration rate (eGFR), urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…However, there are few studies that have elucidated whether minerals are relevant factors influencing Hcy metabolic enzymes. Sadako Matsui's [30] cross-sectional study showed that Zn was negatively correlated to log Hcy in men, but not in women. Esfandiar Heidarian [31] conducted a randomized, double-blind, controlled, crossover study which showed that Zn supplementation reduced serum Hcy and increased vitamin B12 and fol concentrations in T2DM patients with microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies that have elucidated whether minerals are relevant factors influencing Hcy metabolic enzymes. Sadako Matsui's [30] cross-sectional study showed that Zn was negatively correlated to log Hcy in men, but not in women. Esfandiar Heidarian [31] conducted a randomized, double-blind, controlled, crossover study which showed that Zn supplementation reduced serum Hcy and increased vitamin B12 and fol concentrations in T2DM patients with microalbuminuria.…”
Section: Introductionmentioning
confidence: 99%